Smart Public Transport System With Route Optimization - Tan, Jing Hung (Universiti Sains Malaysia, 2018)
Nowadays, transportation is a necessity for urban area citizen. The most common travelling means for them are public transports such as bus. In public bus transportation system, there is a flaw of lack of real time information to the passengers. Buses are often delayed in urban area due to the traffic condition during peak hour. The delay and long waiting period are inefficient and time wasting for the travelers. The experience of the travelers can be improved if real time information of the bus system such as current location, estimate time arrival to the designated station and traffic condition are provided with easier access for the passengers. With the provided information, travelers will be able to find alternate choices for buses depending of the circumstances. A smart transportation system has been proposed where travelers able to obtain real time information of the buses with mobile phone application. In this present scenario, a Global Positioning System (GPS) based system is designed to identify the location of the bus and send it to a database store at Firebase Realtime Database via wireless network. The Google Maps API is used to get the optimized route and display on the map in the Smartphone application. Thus, users will be able to continuously monitor a moving vehicle on demand using the Smartphone application and determine the estimated distance and time for the vehicle to arrive at a given destination.